EXTRACTION AND PROPERTY STUDIES OF COENZYME Q10 FROM RECOMBINANT AGROBACTERIUM TUMEFACIENS - Phuong, Nguyen Viet; Thu, Dang Thi; Son, Luu Hong; Hanh, Nguyen Thi Phuong; Phong, Truong Quoc (Vietnam Journal of Science and Technology, 2015)
In this report, some results of extraction and characterization of CoQ10 from recombinant A. tumefaciens are presented. Four different cell breaking methods (sonication, acidic treatment, ethanol treatment, and enzymatic lysis) in combination with the extracting steps were carried out to extract CoQ10 and the results showed that ethanol treatment was the most efficient method. Appropriate conditions for CoQ10 extraction were 25 oC, 24 hours incubation and ethanol solvent/biomass ratio of 10:1 (ml/g). Characterization of extracted CoQ10 showed that CoQ10 was sensitive to light, but stable in the temperature ranges of 4 – 60 oC and the pH range of 6.0 – 9.0. Obtained results in present study should be applied in the large scale for CoQ10 extraction, providing the CoQ10 product for testing production of functional foods.